(untitled) (International Journal of Engineering and Computer Science, 2014)
Ad hoc networks are characterized by multi-hop wireless connectivity, frequently changing network topology and the need for efficient dynamic routing protocols plays an important role. Comparison of the performance of two prominent on-demand routing protocols for mobile ad hoc networks: Dynamic Sequence Distance Vector (DSDV) Routing Protocol, Optimized Link State Routing (OLSR) Protocol. A detailed simulation model with MAC and physical layer models is used to study the interlayer interactions and their performance implications. This paper demonstrate that even though OLSR and DSDV share similar on-demand behaviour, the differences in the protocol mechanisms can lead to significant performance differentials. Overview of two on demand routing protocols DSDV and OLSR based on packet delivery ratio, normalized routing load, normalized MAC load, average end to end delay by varying the number of sources, speed and pause time. Reliable transport protocols such as TCP are tuned to perform well in traditional networks where packet losses occur mostly because of congestion. However, networks with wireless and other lossy links also suffer from significant losses due to bit errors and handoffs. TCP responds to all losses by invoking congestion control and avoidance algorithms, resulting in degraded end-to-end performance in wireless and lossy systems. In this Paper, comparison of several schemes designed to improve the performance of TCP in such networks is included.